2013
DOI: 10.1016/j.exer.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ maintenance attenuates light induced photoreceptor degeneration

Abstract: Light-induced retinal damage (LD) occurs after surgery or sun exposure. We previously showed that zinc (Zn2+) accumulated in photoreceptors and RPE cells after LD but prior to cell death, and pyruvate or nicotinamide attenuated the resultant death perhaps by restoring nicotinamide adenine dinucleotide (NAD+) levels. We first examined the levels of NAD+ and the efficacy of pyruvate or nicotinamide in oxidative toxicities using primary retinal cultures. We next manipulated NAD+ levels in vivo and tested the affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Moreover, the retinal dysfunction associated with light-induced degeneration can be partially rescued with NMN. These findings offer powerful therapeutic avenues for degenerative diseases of the eye and are supported by past studies exploring the therapeutic applications of NAD + supplementation in light-induced degeneration (Bai and Sheline, 2013), noise-induced hearing loss (Brown et al, 2014), and high-fat diet- and age-induced metabolic complications (Canto et al, 2012; Ramsey et al, 2008; Stein and Imai, 2014; Yoshino et al, 2011). …”
Section: Discussionmentioning
confidence: 58%
“…Moreover, the retinal dysfunction associated with light-induced degeneration can be partially rescued with NMN. These findings offer powerful therapeutic avenues for degenerative diseases of the eye and are supported by past studies exploring the therapeutic applications of NAD + supplementation in light-induced degeneration (Bai and Sheline, 2013), noise-induced hearing loss (Brown et al, 2014), and high-fat diet- and age-induced metabolic complications (Canto et al, 2012; Ramsey et al, 2008; Stein and Imai, 2014; Yoshino et al, 2011). …”
Section: Discussionmentioning
confidence: 58%
“…Exogenous NAD + supplement has been reported to protect cell from death induced by oxidative stress 17 23 . Besides, study on the light-induced retinal damage shows that NAD + treatment attenuates photoreceptor degeneration and RPE cell death triggered by zinc toxicity, a result from pathologic light exposure 24 25 . All these studies suggest that NAD + might be a novel cytoprotective agent against oxidative stress or zinc toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that oxidative stress or zinc toxicity can induce DNA damage and cell death by causing intracellular NAD + depletion or ATP depletion 24 25 26 27 . In the present study, neither NAD + depletion by measurement of intracellular NAD + levels and NAD + /NADH ratios nor inhibition of NAD + synthesis by measurement of gene expression of seven enzymes involved in NAD + biosynthesis was detected in the RPE cells treated with 300 μM H 2 O 2 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen peroxide and nitric oxide have been reported to promote Zn 2+ release from intracellular Zn 2+ stores in several cell types. (12,(25)(26)(27) Knoch et al (28) demonstrated that peroxynitrite triggers Zn 2+ liberation, leading to Zn 2+ -dependent neuronal cell death. NTAPP irradiation generates ROS/RNS to produce peroxynitrite, which reacts with protein and causes protein nitration.…”
Section: Discussionmentioning
confidence: 99%